Strong Synergism of Palmatine and Fluconazole/Itraconazole Against Planktonic and Biofilm Cells of Candida Species and Efflux-Associated Antifungal Mechanism - Wang, Tianming; Shao, Jing; Da, Wenyue; Li, Qianqian; Shi, Gaoxiang; Wu, Daqiang; Wang, Changzhong (Frontiers in Microbiology, 2018)
Fungal infections caused by Candida albicans and non-albicans Candida (NAC) species are becoming a growing threat in immunodeficient population. The resistance to one or more than one conventional antifungal agents contributes greatly to the widespread propagation of Candida infections. The severity of fungal infection requires the discovery of novel antimycotics and the extensive application of combination strategy. In this study, a group of Candida standard and clinical strains including C. albicans as well as several NAC species were employed to evaluate the antifungal potentials of palmatine (PAL) alone and in combination with fluconazole (FLC) and itraconazole (ITR) by microdilution method, checkerboard assay, gram staining and spot assay. Followed by the survey of rhodamine 6G efflux, the expressions of transporter-related genes, namely CDR1, CDR2, MDR1 and FLU1 were analyzed by RT-PCR. The susceptibility test showed that PAL presented strong synergism with FLC and ITR with FICI in a range of 0.0049-0.75 for PAL+FLC and 0.0059-0.3125 for PAL+ITR in planktonic cells, 0.125-0.375 for PAL+FLC and 0.0938-0.3125 for PAL+ITR in biofilms. The susceptibility results were also confirmed by gram staining and spot assay. After combinations, a vast quantity of rhodamine 6G were pumped out as considerable red fluorescence was accumulated intracellularly, and the expressions of CDR1, CDR2, MDR1 and FLU1 were inhibited by 3.62-, 3.91-, 5.79-, and 4.86-fold of decreases. These results indicated that PAL is a decent antifungal synergist to promote the antifungal efficacy of azoles (such as FLC and ITR) which might be associated with the inhibition of efflux pumps and the elevation the intracellular concentration of drugs.